Synthesis of Core‐Shell Au@TiO2@C Nanoparticles and Their Photocatalytic Properties for the Degradation of Rhodamine B Under Simulated‐Solar Light. Issue 32 (27th August 2020) - Wang, Xue‐qin; Li, Dong‐ying; Wang, Shi‐peng; Azad, Fahad; Su, Shi‐chen
Abstract: A simple method to synthesize Au@TiO2 @C core‐shell sandwich nanoparticles by hydrolysis and depositing carbon quantum dots (CQDs) is reported. The photocatalytic activity of the synthesized material was tested via degrading Rhodamine B (RhB) under simulated‐solar light irradiation. The degradation rate was found in the following order: Au@TiO2 @C > P25 > Au@TiO2 > TiO2 . The superior photocatalytic of Au@TiO2 @C was attributed to synergistic effect of Au and CQDs. The CQDs layer coated outside benefits in improving absorption efficiency of solar light host and separation of electron‐holes pairs. The Au core can accelerate transfer process of photo excitons which can facilitate photocatalytic reaction. Abstract : In this work, Au@TiO2 @C core‐shell nanoparticles were prepared via a simple method. Their photocatalytic properties were studied by the degradation of Rhodamine B under simulated‐solar light.